2017
DOI: 10.1186/s12967-017-1223-7
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin-induced necroptosis is enhanced by the inhibition of autophagy in non-small cell lung cancer cells

Abstract: BackgroundShikonin, a natural naphthoquinone pigment purified from Lithospermum erythrorhizon, induces necroptosis in various cancer types, but the mechanisms underlying the anticancer activity of shikonin in lung cancer are not fully understood. This study was designed to clarify whether shikonin causes necroptosis in non-small cell lung cancer (NSCLC) cells and to investigate the mechanism of action.MethodsMultiplex and caspase 8 assays were used to analyze effect of shikonin on A549 cells. Cytometry with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 40 publications
1
51
0
1
Order By: Relevance
“…Shikonin (Fig. 2) is an active naphthoquinone, which is derived from the dried root of Lithospermum erythrorhizon, Arnebia euchroma and Arnebia guttata, and it possesses anti-oxidative, anti-inflammatory, and anti-cancer activities [591][592][593][594]. It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600].…”
Section: Shikoninmentioning
confidence: 99%
See 2 more Smart Citations
“…Shikonin (Fig. 2) is an active naphthoquinone, which is derived from the dried root of Lithospermum erythrorhizon, Arnebia euchroma and Arnebia guttata, and it possesses anti-oxidative, anti-inflammatory, and anti-cancer activities [591][592][593][594]. It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600].…”
Section: Shikoninmentioning
confidence: 99%
“…It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Shikonin (SK), which is isolated from Lithospermum erythrorhizon, has been reported to possess various therapeutic effects, including anti-inflammation, 12,13 antiischemia/reperfusion injury, 14,15 and anti-cancer. 16,17 SK has minimal harm to normal cells and has anti-cancer effects on various tumor cells. [18][19][20] Zhou et al 21 showed that SK induces glioma cell necroptosis by increasing intracellular ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin, a phytochemical naphthoquinone isolated from the roots of the Chinese herbs Lithospermum erythrorhizon, has a significant cytotoxic vigor, suppressing of tumor cell growth and inducing apoptosis in several lines of cancer cells both in vivo and in vitro . Shikonin has been shown to kill certain cancer cells such non‐small cell lung cancer (NSCLC) cells through a number of possible mechanisms and could bypass cancer drug resistance …”
Section: Introductionmentioning
confidence: 99%